Next-Generation Exterior Painting: A Prototype Model for High-Rise Buildings with ESP32 Wireless Control - Mohanasundaram, Anthony; Shakeel, Mohammed (International Journal of Architectural Engineering Technology, 2023)
This paper addresses the need for innovative solutions in exterior painting processes for high-rise buildings. The intention is to develop a prototype model that not only automates the painting procedure but also enhances efficiency, safety, and the overall quality of the process. The methodology involves the integration of ESP32 wireless control technology, allowing for automation through either Wi-Fi or cloud control. The key components of the model include a 240V, 1hp single-phase hoisted motor for vertical movement along the building façade and a 12V PMDC square geared motor for the operation of painting arms that apply paint to the wall. A contactless painting approach is adopted using a sprayer instead of traditional brushes or rollers. The results of the model's painting operations demonstrate significant reductions in time and costs compared to traditional methods, along with improvements in safety and overall painting quality. Notably, the model is designed to adapt to diverse climate conditions and accommodate various building sizes and shapes. This proposed automated exterior painting model holds immense potential for revolutionizing conventional practices, providing a safer, more efficient, and cost-effective solution for a wide range of building structures.